2018
DOI: 10.1108/mf-01-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Market timing and pseudo market timing: an empirical examination of IPOs in India

Abstract: Purpose The purpose of this paper is to examine the impact of market timing and pseudo market timing on equity issuance decisions of IPOs in an emerging economy – India. Indian new issues market provides a perfect setting to test market timing against pseudo market timing due to two reasons. First, the US literature shows that most underpriced IPOs are highly overvalued and in India, the authors have the evidence of underpricing of IPOs. But whether Indian IPOs are overvalued or not it is yet to be tested. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Since the liberalization reforms of 1992, the Indian capital market has evolved tremendously (Saith, 2008;Sayed, 2017;Dayanandan and Sra, 2018;Tiwari and Vidyarthi, 2018). Indian investors, regulators and government introduced and adopted various measures to improve the institutional settings [1] in the country (Wadhwa and Reddy, 2018;Saith, 2008). Indian capital markets are regulated and monitored by the Ministry of Finance, The Securities and Exchange Board of India and the central bank of India, Reserve Bank of India.…”
Section: Introductionmentioning
confidence: 99%
“…Since the liberalization reforms of 1992, the Indian capital market has evolved tremendously (Saith, 2008;Sayed, 2017;Dayanandan and Sra, 2018;Tiwari and Vidyarthi, 2018). Indian investors, regulators and government introduced and adopted various measures to improve the institutional settings [1] in the country (Wadhwa and Reddy, 2018;Saith, 2008). Indian capital markets are regulated and monitored by the Ministry of Finance, The Securities and Exchange Board of India and the central bank of India, Reserve Bank of India.…”
Section: Introductionmentioning
confidence: 99%
“…frontier approach (2005) has characterized "hot issue" markets by high IPO volumes and high levels of initial return and therefore these two dummy variables are taken to distinguish between hot and cold market condition of new issues market activity (Reber and Vencappa, 2016;Wadhwa and Syamala, 2018). In this study, we test the following hypothesis: H7.…”
Section: Stochasticmentioning
confidence: 99%
“…Dhamija and Arora (2017) examined 377 IPOs in India offered during 2005–2015 found that the lead manager prestige, market conditions and market sentiment have no effect on IPO performance. Wadhwa and Syamala (2018) found that in India, at the aggregate level, firm-specific market timing, aggregate market timing, and pseudo-market timing are important factors.…”
Section: Literature Reviewmentioning
confidence: 99%